(untitled) (Nigerian Journal of Technology, 2005)
The dynamic response (natural frequency) of tall building frame models which permit joint ration and the inclusion of the columns axial load were investigated. The stiffness co-efficient of axial members were modified by the use of relevant stability functions through which the contributions of the axial forces were reflected. Comparisons of the responses of models with flexible horizontal members with the exclusion and /or inclusion of the columns axial loads to those of identical frames modeled as shear frame s and considering the buildings as multi degree of freedom systems, based on numerical results were made. The results showed that (a) model with no restriction on joint rotations gave improved results, (b) the inclusion of the axial loads further improved the result and hence, the models, (c) The axial load effect became more significant as the building got ²taller² and (d) at beam to column rigidity (EI) rations below 12 the sear frame gave result s that different by more than 5% from those obtained using the improved models. It is, therefore, recommended that for tall buildings with low horizontal to vertical member rigidity ratios models which permit flexibility of members and joint rotation should be used. For very tall frames, the axial loads should not be ignored.